Empire of the air the men who made radio - Lewis, Tom (HarperPerennial, 1993)
The faith in the future. The will in the future. The will to succeed. What wireless is yer to Be. Sarnoff and Marconi : inventing a legend. Wireless goes to war. Releasing the art : the creation of RCA. Snapshots from the fist age of broadcasting. Court fght. The godlike presence. Armstrong and the FM revolution. The wizard war. Until I'm dead or broke. Victories great and small. The empire in decline...